Pengaruh Online Costumer Review Dan Costumer Rating Terhadap Minat Beli di Tiktok Shop (Studi pada Mahasiswa FEB Universitas Islam Malang) - Qadaraski Saleh; Budi Wahono; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of Online Customer Reviews and Customer Ratings on Interest in Buying Tiktok Shop Products. The sample used was 2019 UNISMA Management Department students with a total of 85 people. Online Customer Reviews and ratings are included in the independent variables, while purchase intention is the dependent variable. Data collection was carried out using a questionnaire given to respondents with answer choices from strongly agree to strongly disagree. The data obtained were analyzed using Parametric Inferential Statistical analysis with SPSS version 25. The analysis process was carried out using several processes, namely, normality test, classical assumption test, multiple linear regression, hypothesis testing, and coefficient of determination. The results of research on Online Customer Reviews and Online Customer Ratings have a partial and simultaneous effect. Therefore, it can be concluded that Online Customer Reviews and Customer Ratings are able to influence the buying interest of Online Shop users, especially Tiktok Shops. Keywords: Customer Reviews, Customer Ratings, Purchase Intention